The Salernitan school of medicine: Women, men, and children. A syndromological review of the oldest medical school in the western world1. Issue 4 (26th February 2013) - Della Monica, Matteo; Mauri, Roberto; Scarano, Francesca; Lonardo, Fortunato; Scarano, Gioacchino
Abstract Ever since the 9th century during the High Middle Ages, the "Schola Medica Salernitana, " believed to be the first medical school in the western world, flourished in Salerno, a city in southern Italy. Although an important role is attributed to several men of this school, who were recognized as wise and learned doctors, modern historiography has also reevaluated and extolled the praiseworthy role of women. Contrary to the common beliefs and expectations of a woman's "place" at the time, these women were fully titled physicians. Attention was also paid to the health and welfare of children. However, there are no apparent references to physical disabilities, a mysterious omission that seems incompatible with an institution that stood as a beacon of knowledge for centuries. Mysteries, discoveries, and potential hidden messages are mingled in a fascinating medieval codex yet to be fully deciphered. The medical school reached its maximum splendor between the years of 1000 and 1300 AD. After alternating fortunes, the Salernitan institution began a slow decline due to the explosive development of other universities, such as those in Paris, Bologna, Padua, and most significantly, the nearby University of Naples. It was eventually closed by the King of Naples, Joachim Murat, November 29, 1811. © 2013 Wiley Periodicals, Inc.